Subjetividad, salud mental y neoliberalismo en las políticas públicas de salud en Colombia (2023)
The investigation is held in a psychoanalytic logic, the first step is the emergence of three significant: subjectivity, mental health and neoliberalism. In a second step, intersect as reflected in Decree 3039 of 2007 by which the public health national plan 2007/2010 is adopted, and the document Guidelines for Public Policy in Mental Health, and its relationship with neoliberalism.